PERENCANAAN PEMBANGUNAN BERBASIS RESPONSIF GENDER DI DESA PELANGKO KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU PADA TAHUN 2015 - Hikmah Aidil Fitra; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Community linkages in gender-responsive development process basedplanning process in Pelangko Village in 2015 are still low, lack of involvement ofwomen representatives in musrenbangdes process, and suggestions from eachgender is still dominated by male gender, it shows the different role and socialrelation between men and womenThe formulation of the problem in this research is how the implementationprocess of responsive based development planning and what are the constrainingfactors in gender responsive development planning in Pelangko Village, KelayangSub-district, Indragiri Hulu Regency in 2015.This study aims to find out the process of implementing gender-responsivedevelopment planning and to know the inhibiting factors in gender-responsivedevelopment based planning in Pelangko Village, Kelayang Sub-district, IndragiriHulu Regency in 2015.This research uses qualitative research method with descriptive researchtype which describes about problem and solving to research subject with clearand detail.The result of this research is this research found that the process ofimplementation of gender-based village development planning village in PelangkoVillage, Kelayang Sub-district, Indragiri Hulu Regency is done with thesuggestion of women's principal need, empower and representation of woman ingovernment affair while gender-based budgeting Inhibiting factor in villagemusrenbang based on gender are: Still influenced by patriarchy culture factor,lack of response and responsiveness in politics and government, lack ofexperience, shy opinion, and low human resource in terms of education.Keywords: Representation of Budgeting, Responsive Gender